2020
DOI: 10.1002/smll.202000749
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Laser Manufacture of Stable, Efficient Ultrafine Noble Metal Catalysts Mediated with MOF Derived High Density Defective Metal Oxides

Abstract: subdivision reduces cost, but nano-and atomic-scale PGM catalysts can suffer from severe aggregation and degradation under practical use conditions. [1][2][3][4][5] This is due to coalescence and Ostwald ripening of metal nanoparticles (MNPs) driven by high surface energy. Catalysts constructed by dispersion of nanosized precious metals on metal oxide supporting particles are widely explored to deal the aggregation issue. [6][7][8][9][10][11][12] However, because of the limited contact between them and the lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…The laser-induced product exhibited high stability and activity for CO oxidation even under long reaction period. 275…”
Section: Photolytic Destructionmentioning
confidence: 99%
See 1 more Smart Citation
“…The laser-induced product exhibited high stability and activity for CO oxidation even under long reaction period. 275…”
Section: Photolytic Destructionmentioning
confidence: 99%
“…Through ultrafast laser vaporization and cooling, Ce-MOFs transformed rapidly, within tens of nanoseconds, into defective CeO 2 nanoparticles that showed strong coupling with well-dispersed ultrasmall noble metal nanoparticles. The laser-induced product exhibited high stability and activity for CO oxidation even under long reaction period …”
Section: Photolytic Destructionmentioning
confidence: 99%
“…The spectrum and curve obtained by deconvolution simulation are shown in Figure S2. After careful deconvolution from the overlapped peaks of Pt 4f and Al 2p, peaks located at binding energies of 71.2 and 74.5 eV were assigned to Pt 4f 7/2 and Pt 4f 5/2 of Pt 0 on the Pt/MgAlO adsorbent, respectively. , When the Ni was introduced into the Pt/MgAlO adsorbent, the binding energies of Pt 4f 7/2 and Pt 4f 5/2 shifted to 71.4 and 74.7 eV (Figure B). This result revealed that the electron binding energy of Pt moves to higher binding energy.…”
Section: Resultsmentioning
confidence: 99%
“…There are three common ways to introduce nucleation and anchoring sites in supports: installing organic functional groups, heteroatom doping and creating defect sites. [30][31][32][33][34][35] Organic functional groups can bind the metal ions in the precursor solution. It is a common method to capture the metal ions and anchor the resulting UMNPs in organic or hybrid supports, such as metal organic frameworks (MOFs) and covalent organic frameworks (COFs).…”
Section: The Electronic Confinement Effects Originated From the Intermentioning
confidence: 99%
“…Jiang et al used Pt ion-doped Ce-MOFs to create Pt UMNPs (< 2 nm) supported on CeO 2 particles (s-Pt/CeO 2 ) through an ultrafast laser induced reduction. 34 In this process, the MOF crystals absorb laser photons and generate high pressure and high temperature, causing the pyrolysis of organic liners and reduction of metal ions. Nanocrystalline CeO 2 particles with abundant defects on their surface were in situ precipitated, which serve as anchoring sites for Pt UMNPs.…”
Section: Synthesis Of Umnps Supported By Metal Oxide/sulfidementioning
confidence: 99%